MORPHOLOGICAL STUDIES ON THE FEMUR, TIBIOTARSUS AND FIBULA OF PEAHEN (Pavo cristatus) - A.R. Sreeranjini (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted on the femur, tibiotarsus and fibula of a peahen. The femur was extremely light compared to that of chicken and duck with curved shaft, two extremities and four surfaces. The proximal and distal extremities were almost of equal size with large number of pneumatic foramina. The proximal extremity presented distinct head and neck. Distal extremity contained a trochlea and two condyles. The condyles were separated by a wide intercondyloid groove. The lateral condyle was larger and was placed at a lower level. The caudolateral part of lateral condyle presented a facet for articulation with fibula. The femur of peacock presented all morphological features that were suited to make movements like protraction, retraction, abduction, adduction and rotation. The tibiotarsus was the largest of the leg bones and was twice longer than femur. It presented a long shaft and two extremities. Lateral surface of the shaft near the proximal extremity furnished an indistinct fibular crest. Near the distal extremity, dorsal aspect of the shaft presented the extensor canal. The proximal extremity contained larger medial and smaller lateral condyles. From the proximal articular surface, a short and stump cnemial crest extended ventrally and medially. The distal extremity of tibiotarsus presented large lateral and small medial condyle separated by intercondyloid fossa. The condyles continued caudally to constitute a wide grooved trochlea. The fibula was a reduced long bone with distinct head and rudimentary shaft. It terminated freely at about the middle of the shaft of tibiotarsus. The long tibiotarsus of peahen indicated adaptive features for bipedalism and running whereas, the highly reduced fibula and fusion of tibia with proximal row of tarsals to form tibiotarsus were indicative of adaptations for flight.